The Effect of Professional Skepticism, Independence and Auditor Ethics on Fraud Prevention by Moderating Audit Quality (Study at Public Accountant Firm Jojo Sunarjo and Partners) - Aprianto, Hary; Nur, Basyiruddin; Karsam, Karsam (Dinasti Publisher, 2026)
The purpose of this research is to determine the influence of Professional Skepticism, Independence, and Auditor Ethics on Fraud Prevention moderated by Audit Quality. The research method used is a quantitative research approach. The data for this research was obtained from the distribution of questionnaires to all JS & R Public Accountant Offices, totaling 100 Auditor respondents. The analysis technique used was PLS SEM version 4. Based on the research results, it is stated that Professional Skepticism has a positive and significant effect on Fraud Prevention with a path coefficient value of 0.307 and a p-value of 0.018. Independence has a positive and significant effect on Fraud Prevention with a path coefficient value of 0.238 and a p-value of 0.013. Auditor Ethics has a significant positive effect on Fraud Prevention with a path coefficient value of 0.256 and a p-value of 0.002. Audit Quality moderates the effect of Professional Skepticism on Fraud Prevention with a path coefficient value of 0.286 and a p-value of 0.004. Audit Quality moderates the effect of Independence on Fraud Prevention with a path coefficient value of -0.304 and a p-value of 0.025. Audit Quality does not moderate the effect of Auditor Ethics on Fraud Prevention with a path coefficient value of 0.028 and a p-value of 0.374.